From victims to survivors: resilience in the Sahrawi refugee camps - Guarch-Rubio, Marta (Revista de victimología, 2023)
Being a long-term refugee undermines the confidence to overcome this legal status. As time passes people might feel trapped in time and in space and both factors contribute to their learned helplessness. What can they do to be relieved from it? Resilience elements might be buffers to deal with it. This exploratory study focuses on the evaluation of the degree of resilience in a sample of people residing in the Sahrawi refugee camps in Tindouf (Algeria). Twenty-nine women and thirteen men, with an average age of 34.50 years were assessed. At the time they were evaluated, they had been living in a protracted refugee condition for a mean of 30.71 years. They were interviewed using a specific designed clinical questionnaire and the Resilience Scale by Wagnild and Young (1993). According to the data, 38.09% of the refugees scored a low level of resilience; 33.33% a medium level; and 28.57% a high level. Being born in a refugee camp and having little hope for the future depicted a negative correlation with coping strategies. Moreover, 50% of the participants cited fears and insecurities associated with the political situation that keeps them as refugees whereas 54.8% of them expressed hope for a positive future. No gender and age differences were found in the resilience capacity. This research contributes to the literature and shines a light on the emotional well-being of those most marginalised populations.